PENGARUH PENGELUARAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP REPUTASI PERUSAHAAN - Fadhila, Febri Luthfi; Widiastuty, Erna (AKUNTANSI DEWANTARA, 2024)
The purpose of this research is to provide empirical evidence the effect of corporate social responsibility expenditure on corporate reputation. The sample are 690 firm-years from the Indonesia Stock Exchange (IDX). The observation year is 2016-2021. The corporate social responsibility expenditure is measured by monetary unit in Rupiah. The firm reputation is measured by market capitalization. We also use ROA and firm size as control variables. The results of the study show that corporate social responsibility expenditure has a significant positive effect on corporate reputation. The implication of this research is that public companies need to consider that spending CSR and disclose the information have a significant effect on the company's reputation in the future.